RETRACTED: Using machine learning to forecast hard drive failures - Kodatsky Nikita; Revyakina Elena; Gazizov Andrei; Gunko Vitaliy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001